Kugukigi: Cookies made just for you - Aguilan, Carl Justine, Bose, Darryl, Figueroa, Pamela, Galvez, Joshua, Gebana, Jillian Dana, Mesa, John Paulo, Miaral, Frances Sofia, Mora, Maria Angela, Moran, Dionel Angelo, Navarro, Alrietiel Josh, Pinlac, Colline Joanne, Retardo Aubrey Mae, Santos, Allysa, Tagle, Frances Avigail 4 0 16; 5
u
Feasibility Study: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2